Dietary Patterns and Risk of Inflammatory Bowel Disease in Europe: Results from the EPIC Study. Issue 2 (30th December 2015) - Racine, Antoine; Carbonnel, Franck; Chan, Simon S. M.; Hart, Andrew R.; Bueno-de-Mesquita, H. Bas; Oldenburg, Bas; van Schaik, Fiona D. M.; Tjønneland, Anne; Olsen, Anja; Dahm, Christina C.; Key, Timothy; Luben, Robert; et al.
Abstract : Background: Specific nutrients or foods have been inconsistently associated with ulcerative colitis (UC) or Crohn's disease (CD) risks. Thus, we investigated associations between diet as a whole, as dietary patterns, and UC and CD risks. Methods: Within the prospective EPIC (European Prospective Investigation into Cancer) study, we set up a nested matched case–control study among 366, 351 participants with inflammatory bowel disease data, including 256 incident cases of UC and 117 of CD, and 4 matched controls per case. Dietary intake was recorded at baseline from validated food frequency questionnaires. Incidence rate ratios of developing UC and CD were calculated for quintiles of the Mediterranean diet score and a posteriori dietary patterns produced by factor analysis. Results: No dietary pattern was associated with either UC or CD risks. However, when excluding cases occurring within the first 2 years after dietary assessment, there was a positive association between a "high sugar and soft drinks" pattern and UC risk (incidence rate ratios for the fifth versus first quintile, 1.68 [1.00–2.82]; P trend = 0.02). When considering the foods most associated with the pattern, high consumers of sugar and soft drinks were at higher UC risk only if they had low vegetables intakes. Conclusions: A diet imbalance with high consumption of sugar and soft drinks and low consumption of vegetables was associated with UC risk. Further studies are needed to investigate whether microbiota alterations or other mechanisms mediate this association.